Conical intersection dynamics of the primary photoisomerization event in vision. - Polli, D; Altoè, P; Weingart, O; Spillane, K; Manzoni, C; Brida, D; Tomasello, G; Orlandi, G; Kukura, P; Mathies, R; Garavelli, M; Cerullo, G (2010)
Ever since the conversion of the 11-cis retinal chromophore to its all-trans form in rhodopsin was identified as the primary photochemical event in vision, experimentalists and theoreticians have tried to unravel the molecular details of this process. The high quantum yield of 0.65 (ref. 2), the production of the primary ground-state rhodopsin photoproduct within a mere 200 fs (refs 3-7), and the storage of considerable energy in the first stable bathorhodopsin intermediate all suggest an unusually fast and efficient photoactivated one-way reaction. Rhodopsin's unique reactivity is generally attributed to a conical intersection between the potential energy surfaces of the ground and excited electronic states enabling the efficient and ultrafast conversion of photon energy into chemical energy. But obtaining direct experimental evidence for the involvement of a conical intersection is challenging: the energy gap between the electronic states of the reacting molecule changes significantly over an ultrashort timescale, which calls for observational methods that combine high temporal resolution with a broad spectral observation window. Here we show that ultrafast optical spectroscopy with sub-20-fs time resolution and spectral coverage from the visible to the near-infrared allows us to follow the dynamics leading to the conical intersection in rhodopsin isomerization. We track coherent wave-packet motion from the photoexcited Franck-Condon region to the photoproduct by monitoring the loss of reactant emission and the subsequent appearance of photoproduct absorption, and find excellent agreement between the experimental observations and molecular dynamics calculations that involve a true electronic state crossing. Taken together, these findings constitute the most compelling evidence to date for the existence and importance of conical intersections in visual photochemistry.